METHODS FOR IMPROVING THE ENERGY EFFICIENCY OF PUMPING STATIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Improving the energy efficiency of pumping stations is a critical task in modern water supply, irrigation, and industrial systems due to increasing energy costs and the need for sustainable resource management. This study analyzes the main factors affecting energy consumption in pumping stations, including pump selection, operating режимes, hydraulic losses, and control strategies. Particular attention is given to the application of variable frequency drives, optimal scheduling of pump operation, pipeline optimization, and real-time monitoring systems. Comparative evaluation of traditional and energy-efficient solutions demonstrates that significant reductions in electricity consumption and operating costs can be achieved without compromising system reliability. The results highlight the importance of integrated technical and operational measures for enhancing overall performance and extending equipment service life. The findings of this research can be applied in the design, modernization, and management of pumping stations to ensure higher efficiency and sustainability.